Specialty pharmacist integration into an outpatient neurology clinic improves pimavanserin access - Livezey, Sabrina (Ment Health Clin, 2021)
INTRODUCTION: Access to pimavanserin, the only Parkinson disease–related psychosis treatment approved by the FDA, is restricted by insurance requirements, a limited distribution network, and high costs. Following initiation, patients require monitoring for safety and effectiveness. The primary objective of this study was to evaluate impact of specialty pharmacist (SP) integration on time to insurance approval. Additionally, we describe a pharmacist-led monitoring program. METHODS: This was a single-center, retrospective study of adults prescribed pimavanserin by the neurology clinic from June 2016 to June 2018. Patients receiving pimavanserin externally or through clinical trials were excluded. Pre- (June 2016 to December 2016) and post-SP integration (January 2017 to June 2018) periods were assessed. Proportional odds logistic regression was performed to test association of approval time with patient characteristics (age, gender, insurance type) postintegration. Interventions were categorized as clinical care, care coordination, management of adverse event, or adherence. RESULTS: We included 94 patients (32 preintegration, 62 postintegration), 80% male (n = 75) and 96% white (n = 90) with a mean age of 73 years. Median time to approval was 22 days preintegration and 3 days postintegration. Higher rates of approval (81% vs 95%) and initiation (78% vs 94%) were observed postintegration. Proportional odds logistic regression suggested patients with commercial insurance were likely to have longer time to approval compared with patients with Medicare/Medicaid (odds ratio 7.1; 95% confidence interval: 1.9, 26.7; P = .004). Most interventions were clinical (51%, n = 47) or care coordination (42%, n = 39). CONCLUSION: Median time to approval decreased postintegration. The SP performed valuable monitoring and interventions.